Factors Influencing Tax Aggressiveness: Liquidity, Leverage, Earnings Management, Independent Commissioner, Company Size - Nurrahman, Nafal Thorfi; Kuntadi, Cris (Universitas Wiralodra, 2023)
The purpose of this research is to analyze the effect of liquidity, leverage ̧ earnings management, the proportion of independent commissioners, and company size on the level of corporate tax aggressiveness. This study uses the manufacturing industry listed on the Indonesia Stock Exchange in 2010-2011 as the population. By using a purposive sampling technique, 148 data were selected as samples. The results of multiple regression analysis show that earnings management and company size have a significant influence on the level of corporate tax aggressiveness. Meanwhile, for liquidity, leverage, and the proportion of independent commissioners did not show a significant effect on the level of corporate tax aggressiveness.